Mineralogical Characteristics and Color Origin of Nephrite Containing Pink Minerals - Ye Yuan; Youxuan Li; Miao Shi (Crystals)
Recently, a variety of nephrite containing localized pink mineral aggregates has emerged on the market, which is sometimes referred to as “peach blossom jade” by some merchants. Currently, there is limited research on this type of nephrite containing pink minerals, and its detailed mineral composition characteristics and coloration mechanisms remain unclear. In this study, four samples of nephrite containing pink minerals were systematically investigated using conventional gemological tests, as well as modern analytical techniques such as X-ray powder diffraction (XRD), infrared spectroscopy (IR), laser Raman spectroscopy, ultraviolet–visible (UV-Vis) absorption spectroscopy, electron probe microanalysis (EPMA), and X-ray fluorescence spectroscopy (XRF). These techniques were employed to elucidate the mineral composition, chemical composition, spectroscopic features, and coloration origins of the samples. The results indicate that the primary mineral constituent of the samples is tremolite, with accessory minerals including zoisite, muscovite, orthoclase, andesine, diopside, and prehnite. The major chemical components of the samples are SiO2, CaO, and MgO, along with minor amounts of Al2O3, K2O, and FeOT. The overall green hue of the samples is positively correlated with Fe content. The pink mineral present in the samples is predominantly Mn-bearing zoisite, and the pink coloration of zoisite is primarily attributed to the energy level transitions of Mn2+ at approximately 540 nm and 440 nm.